Structural And Semantic Classification Of Conjunctions In English And Uzbek (Texas Journal of Philology, Culture and History, 2025)
This article explores the structural and semantic classification of conjunctions in English and Uzbek. Conjunctions, as crucial grammatical units, perform connective functions at both sentence and discourse levels. While English and Uzbek differ typologically—being an analytic and agglutinative language, respectively—both use conjunctions to express coordination, subordination, causality, contrast, and other logical-semantic relations. Through comparative analysis, this study highlights the structural forms and semantic types of conjunctions in the two languages and offers insights into their similarities and differences in use, function, and frequency.